2017
DOI: 10.3892/etm.2017.4308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of recombinant thrombomodulin on a lipopolysaccharide-induced murine sepsis model

Abstract: Abstract.To evaluate the effect of recombinant human thrombomodulin (rTM) on sepsis, the levels of nucleosome as well as high-mobility group box 1 (HMGB1) and cytokines in sera and peritoneal fluids were measured in a mouse model of lipopolysaccharide (LPS)-induced sepsis after administration of rTM. C57BL/6 mice were intraperitoneally injected with LPS (15 mg/kg; Escherichia coli O111:B4) with or without the intravenous administration of rTM (3 mg/kg; 30 min prior to or 2 h after LPS injection). The survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Nagato et al reported that the intravenous administration of 1 mg/kg of rhTM 30 min prior to sepsis induction significantly improved sepsis survival, and suppressed inflammatory cytokines and HMGB1 elevation in an LPS-treated rat sepsis model 16 . Takehara et al reported that the intravenous administration of 3 mg/kg of rhTM 30 min prior to sepsis induction improved sepsis survival, and suppressed the elevation of inflammatory cytokines and HMGB1 in serum and ascites in an LPS-treated mouse sepsis model 25 . However, these studies used adult rodent sepsis models, and there has been no report investigating the effects of rhTM in an animal model of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Nagato et al reported that the intravenous administration of 1 mg/kg of rhTM 30 min prior to sepsis induction significantly improved sepsis survival, and suppressed inflammatory cytokines and HMGB1 elevation in an LPS-treated rat sepsis model 16 . Takehara et al reported that the intravenous administration of 3 mg/kg of rhTM 30 min prior to sepsis induction improved sepsis survival, and suppressed the elevation of inflammatory cytokines and HMGB1 in serum and ascites in an LPS-treated mouse sepsis model 25 . However, these studies used adult rodent sepsis models, and there has been no report investigating the effects of rhTM in an animal model of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse histone-induced septic model, pretreatment with rTM reduced mortality rates by neutralizing histones ( 20 ). In a rat sepsis/peritonitis model ( 33 ) and a murine LPS-induced septic model ( 34 ), rTM controlled sepsis-related immunothrombosis by limiting abnormal hemostasis and NET formation.…”
Section: Experimental Evidence Of Rtm-mediated Resolution Of Inflammamentioning
confidence: 99%
“…Although the anti-inflammatory and cytoprotective effects deployed by rsTM to counter inflamed endothelial cells have been known [3,5,6], the impact of rsTM on endothelial cellular stiffening under inflammatory conditions remains elusive. Therefore, we investigated whether rsTM suppresses endothelial cellular stiffening during LPS-mediated sterile inflammation.…”
Section: Rstm Reduces Lps-induced Endothelial Cellular Stiffeningmentioning
confidence: 99%
“…Thus, endothelial cell dysfunction is a cause of the vascular lesions associated with functional and structural abnormalities in vascular vessels. Thrombomodulin (TM) is an anticoagulant protein that is predominantly expressed on the surface of endothelial cells [1][2][3]. TM directly binds to thrombin and inhibits thrombin procoagulant activity [1,2].…”
Section: Introductionmentioning
confidence: 99%